New Lignanamides with Antioxidant and Anti-Inflammatory Activities Screened Out and Identified from Warburgia ugandensis Combining Affinity Ultrafiltration LC-MS with SOD and XOD Enzymes - Xiao-Cui Zhuang; Gui-Lin Chen; Ye Liu; Yong-Li Zhang; Ming-Quan Guo (Antioxidants, 2021)
Warburgia ugandensis, also known as “green heart,” is widely used for the treatment of various diseases as a traditional ethnomedicinal plant in local communities in Africa. In this work, 9 and 12 potential superoxide dismutase (SOD) and xanthine oxidase (XOD) ligands from W. ugandensis were quickly screened out by combining SOD and XOD affinity ultrafiltration with LC-MS, respectively. In this way, four new lignanamides (compounds 11–14) and one new macrocyclic glycoside (compound 5), along with three known compounds (compounds 1, 3, and 7), were isolated and identified firstly in this species. The structures of the new compounds were elucidated by spectroscopic analysis, including NMR and UPLC-QTOF-MS/MS. Among these compounds, compound 14 showed the highest 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzthiazoline)-6-sulfonic acid (ABTS) radical scavenging activities, and total ferric-reducing antioxidant power (FRAP) with IC50 values of 6.405 ± 0.362 µM, 5.381 ± 0.092 µM, and 17.488 ± 1.625 mmol TE/g, respectively. Moreover, compound 14 displayed the highest inhibitory activity on cyclooxygenase-2 (COX-2) with IC50 value of 0.123 ± 0.004 µM, and the ranking order of other compounds’ IC50 values was 13 > 11 > 7 > 1 > 12. The present study suggested that lignanamides might represent interesting new characteristic functional components of W. ugandensis to exert remarkable antioxidant and anti-inflammatory activities. Moreover, compound 14, a new arylnaphthalene lignanamide, would be a highly potential natural antioxidant and anti-inflammatory agent from W. ugandensis.